Penerapan Zahir Accounting Dalam Pengolahan Data Keuangan PT. Aneka Tusma - Azironia, Aghita; Ade Fitria Lestari, Ade Fitria; Amalia, Hilda; Puspita, Ari (Jurnal Sistem Informasi Akuntansi, 2024)
Efficient and accurate financial data processing is a crucial factor in maintaining a company's financial stability.maintaining the company's financial stability. PT Aneka Tusma, a company that selling various types of home accessories and furniture products, realises the importance of good of good financial data management to support operational activities and make the right decisions. making the right decisions. This research aims to examine the use of Zahir Accounting Version 6 as a tool for financial data processing at PT. Aneka Tusma, whose accounting process is currently manual. Zahir Accounting is one of the most popular accounting software in Indonesia, which provides various features and modules to help the recording process, reporting, and financial analysis